THE LEGAL POLITIC OF REGULATION FOR TRADEMARK REGISTRATION SYSTEMS IN INDONESIA - Darwance Darwance; Sudarto Sudarto (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
The development of brand functions which was originally only as a distinguishing element to be more of a reputation, to be the brand that is usually represented by the image, logos, etc., resulting in a brand being one of the triggers for a dispute. Therefore, a number of regulations that provide protection for marks have been issued in Indonesia started with Trademark Law of 1885 published by the Dutch Colonial Government until Law Number 20 of 2016 concerning on Current Marks and Geographical Indications. But, the trademark disputes still occur. This juridical normative research with a legal approach aims to know and analyze the legal politics of trademark registration regulations in Indonesia. The result is that there are weaknesses in the existing regulations regarding on trademark registration, both substantial and procedural. Therefore, it needs to be clearer and more concrete regulations in regulating trademark registration in Indonesia so that trademark disputes can be minimized.